A New Frontier in Ferroptosis-Driven Cancer Treatment - Shang, Tzu-Hsuan; Zheng, Cheng (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Ferro ptosis, as an iron-dependent form of regulated cell death fundamentally controlled by lipid peroxidation, has been discovered to be effective in cancer therapy. However, in contrast to traditional treatment methods such as chemotherapy and radiation, ferroptosis specifically targets and destroys cancerous cells. Nevertheless, ferroptosis faces significant obstacles, including low tumour penetration, off-target toxicity, and poor solubility. Nanotechnology, namely the design of multifunctional nanoparticles (NPs), shows promise in inducing ferroptosis by several mechanisms including Fenton reactions, GPX4 inhibition, transport of lipid peroxides, and photosensitization. Significantly, the configuration of multifunctional NPs instigated ferroptosis, leading to an enhanced drug-loading system, a targeted delivery system for tumours, a synergistic combination system with other cancer therapies, and notably, additional attributes like responsiveness to stimuli. This review explains the advantages of ferroptosis-based cancer therapy over traditional methods and its potential for clinical translation. With the mentioned properties, nanotechnology can now enhance ferroptosis-based cancer therapy, leading to improved and tailored treatment techniques.